2006
DOI: 10.1111/j.1365-2265.2006.02548.x
|View full text |Cite
|
Sign up to set email alerts
|

Application of new homologous in vitro bioassays for human lactogens to assess the actual bioactivity of human prolactin isoforms in hyperprolactinaemic patients

Abstract: The reduced bioactivity of PRL in patients with macroprolactinaemia may further explain the absence of clinical features of hyperprolactinaemia in these individuals. In addition, our findings indicate that species-specificity and sensitivity of the bioassays are determinant factors in the measurement of the intrinsic biological activity of circulating PRL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 40 publications
0
23
0
Order By: Relevance
“…For a long time, the large size of macroprolactin has been proposed to make it unable to cross capillary membranes to reach its target receptors, thus reducing its in vivo activity and explaining the attenuated clinical manifestations [1,[15][16][17][18]. However, results of recent studies have shown that macroprolactin has reduced activity toward its homologous receptor and this altered bioactivity may contribute to the absence of symptoms related to macroprolactin [19,20].…”
Section: Discussionmentioning
confidence: 97%
“…For a long time, the large size of macroprolactin has been proposed to make it unable to cross capillary membranes to reach its target receptors, thus reducing its in vivo activity and explaining the attenuated clinical manifestations [1,[15][16][17][18]. However, results of recent studies have shown that macroprolactin has reduced activity toward its homologous receptor and this altered bioactivity may contribute to the absence of symptoms related to macroprolactin [19,20].…”
Section: Discussionmentioning
confidence: 97%
“…One study examined the correlation between the Nb2 assay and a similar assay using human prolactin receptor. [31] When the predominant form of prolactin was monomeric, the two assays performed similarly; however, when high levels of macroprolactin were present, the Nb2 assay had higher levels than the human based assay. Second, while the bioactivity assay is primarily influenced by prolactin, proliferation also can be stimulated by growth hormone,[15, 26] although the concentrations of growth hormone must be very high to stimulate Nb2 cells and over 80% of the stimulation is due to prolactin.…”
Section: Discussionmentioning
confidence: 99%
“…Macroprolactinemia is characterized by a lack of clinical symptoms of hyperprolactinemia and several studies using different PRL bioassay systems showed that the bioactivity of macroprolactin is low [32, 42, 43]. The epitope mapping using deleted PRL fragments revealed that the binding sites of PRL molecule to anti-PRL autoantibodies reside in N and C terminals of PRL [39].…”
Section: Pathogenic Significancementioning
confidence: 99%